Globalization, spaces, identities and (In) securities / edited by Jyrki Kakonen and Sanjay Chaturvedi - Kakonen, Jyrki (ed.) (New Delhi, 2005)
The politics behind the production of geographical knowledge(s) of 'Globalization' needs to be further explored in a serious and systematic manner. This book argues that it is only by acknowledging the messy nature, fuzzy scale, uneven playing field, and a contextualized as well as temporized nature of Globalization, that implications of this multifaceted phenomena for spaces, identities and (in)securities in Eurasia can be adequately examined. It sounds a note of caution against making Globalization yet another hegemonic theoretical paradigm, after, or along with, Realism, to explain what is going on in the world today.
Keywords: Foreign Relations